Be(ing) prepared: Guide and Scout participation, childhood social position and mental health at age 50—a prospective birth cohort study. Issue 3 (10th November 2016) - Dibben, Chris; Playford, Chris; Mitchell, Richard
Abstract : Background: Mental health is a major concern in many countries. We explore whether youth participation in the Scouts and Guides could protect mental health in later life and in particular whether it might reduce inequalities in mental health associated with early life socioeconomic position. Methods: Using the 1958 birth cohort National Child Development Study, we tested whether Scouts–Guide attendance was associated with mental health (SF-36, Mental Health Index (MHI-5)) controlling for childhood risk factors and interacted with social class. Results: Of the 9603 cohort members, 28% had participated in the Scouts–Guides. The average MHI-5 score was 74.8 (SD 18.2) at age 50. After adjustment, for potential childhood confounders, participation in Scouts–Guides was associated with a better MHI-5 score of 2.22 (CI 1.32 to 3.08). Among those who had not been a Scout–Guide, there was a gradient in mental health at age 50 by childhood social position, adjusting for other childhood risk factors. This gradient was absent among those who had been a Scout–Guide. Scout–Guides had an 18% lower odds of an MHI-5 score indicative of mood or anxiety disorder. The findings appeared robust to various tests for residual confounding. Conclusions: Participation in Guides or Scouts was associated with better mental health and narrower mental health inequalities, at age 50. This suggests that youth programmes that support resilience and social mobility through developing the potential for continued progressive self-education, 'soft' non-cognitive skills, self-reliance, collaboration and activities in natural environments may be protective of mental health in adulthood.